Predicting Dengue Outbreaks in Cambodia - Cousien, Anthony (Emerg Infect Dis, 2019)
In Cambodia, dengue outbreaks occur each rainy season (May–October) but vary in magnitude. Using national surveillance data, we designed a tool that can predict 90% of the variance in peak magnitude by April, when typically <10% of dengue cases have been reported. This prediction may help hospitals anticipate excess patients.